Characterization of a Cytomegalovirus-Specific T Lymphocyte Product Obtained Through a Rapid and Scalable Production Process for Use in Adoptive Immunotherapy - Grau-Vorster, Marta; López-Montañés, María; Cantó, Ester; Vives, Joaquim; Oliver-Vila, Irene; Barba, Pere; Querol, Sergi; Rudilla, Francesc (Frontiers in Immunology, 2020)
Immunosuppressed patients are susceptible to virus reactivation or de novo infection. Adoptive immunotherapy, based on virus-specific T lymphocytes (VST), can prevent or treat viral diseases. However, donor availability, HLA-compatibility restrictions, high costs and time required for the production of personalized medicines constitute considerable limitations to this treatment. Ex vivo rapid and large-scale expansion of VST, compliant with current good manufacturing practice (cGMP) standards, with an associated cell donor registry would overcome these limitations. This study aimed to characterize a VST product obtained through an expansion protocol transferable to cGMP standards. Antigenic stimulus consisted of cytomegalovirus (CMV) pp65 peptide pool-pulsed autologous dendritic cells (DCs) derived from monocytes. G-Rex technology, cytokines IL-2, IL-7, and IL-15, and anti-CD3 and anti-CD28 antibodies were used for culture. At day 14 of cell culture, the final product was characterized regarding T cell subsets, specificity, and functionality. The final product, comprised mainly CD4+ and CD8+ T lymphocytes (49.2±24.7 and 42.3±25.2, respectively). The culture conditions made it possible to achieve at least a 98.89-fold increase in pp65-specific CD3+ IFN-γ+ cells. These cells were specific, as pp65-specific cytotoxicity was demonstrated. Additionally, in complete HLA mismatch and without the presence of pp65, alloreactivity resulted in less than 5% cell lysis. In conclusion, a cGMP scalable process for the generation of a large number of doses of CMV-specific cytotoxic T cells was successfully performed.